THE INFLUENCE OF PRICE PERCEPTIONS, PRODUCT REVIEWS, AND CONVENIENCE ON PURCHASE DECISIONS AT TOKOPEDIA E-COMMERCE - Citaningtyas Ari Kadi, Dian; Ula Ananta Fauzi, Rizal; Ahmad, Arman Hj.; Putri Wardani, Winda (LP2M Institut Teknologi dan Bisnis Asia Malang, 2023)
This study is entitled